Role of subcutaneous suction drain in reducing surgical site infections after emergency laparotomy - Gupta, Poonam; Kumar, Rajesh (International Surgery Journal, 2017)
Background: One of important morbidity postoperatively is surgical site infection and the important cause is collection of blood and serous fluids which can get infected and this factor is even more important in emergency laparotomies. our prospective randomised study compares the incidence of surgical site infection in post emergency abdominal surgical wounds with subcutaneous suction drains versus those in whom drain was not placed. Methods: A prospective interventional study of 100 subjects done in department of surgery at rural tertiary centre. on the basis of exclusion and inclusion criteria patient were randomly selected for cases (with post-operative suction drain) and controls. subcutaneous drain in emergency setting play significant role in reducing the incidence of surgical site infection which is significant statistically. Results: 24% of patients in drain group develop surgical site infections. 50% of patients in non-drain group develop infection. Incidence of infection in drain group was lower than the no drain group (p value 0.05) and was statistically significant. Conclusions: Subcutaneous drain in emergency laparotomy play significant role in reducing the incidence of surgical site infection